ANALISIS POTENSI DAYA HIDRO AIR TERJUN TALUDA’A - Sahlan Buako; Burhan Liputo; Romi Djafar; Yunita Djamalu; Satria Wati Pade (Program Vokasi-Universitas Negeri Gorontalo, 2023)
Mini Hydro Power Plant (PLTM) is a small-scale power plant using hydropower that utilizes the height of the waterfall (head) and the amount of water discharge. Because using water as the primary source, the power produced is irregular due to weather factors, it is necessary to conduct an Analysis to determine the potential energy that Taluda''a waterfall is at peak load. The research was conducted at Taluda'a waterfall, Bone District, Bone Bolango Regency, 65 km from downtown Gorontalo. The type of research used includes descriptive analysis; data sources are data obtained from several existing literature and research results, both experimental research results and survey research or directly in the field related to this research. The development of the analysis of the discharge on the Carrier channel (Headrace) is 8.83 m³ / s, and the water discharge on the rapid pipe (Penstok) is 5.1 m³ / s With a shot of 5.1 m³ / s and a head of 20 meters can generate hydro power of 999.6 kW. The actual charge dramatically affects the amount of energy generated. The Taluda'a PLTM has a 20-meter high head which is relatively low for a discharge of 5.1 m³/s. If the actual charge of the taluda'a PLTM is 40 meters high, the power that can be generated reaches 1.9 MW.